2010
DOI: 10.1590/s0004-27302010000800008
|View full text |Cite
|
Sign up to set email alerts
|

Six new cases confirm the clinical molecular profile of complete combined 17α-hydroxylase/ 17,20-lyase deficiency in Brazil

Abstract: All patients had hypogonadism, amenorrhea and hypertension at diagnosis. Two sisters were found to be 46,XY with both gonads palpable in the inguinal region. All patients presented hypergonadotrophic hypogonadism, with high levels of ACTH (> 104 ng/mL), suppressed plasmatic renin activity, low levels of potassium (< 2.8 mEq/L) and elevated progesterone levels (> 4.4 ng/mL). Three of them, including two sisters, were homozygous for p.W406R mutation and the other three (two sisters and one cousin) were homozygou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
(29 reference statements)
1
7
0
1
Order By: Relevance
“…In the present study, we found 17OHD patients carrying mutations previously described in Brazilian patients [6,25,33] suggesting possible founder effect. The intron 2 IVS2-2A > C mutation occurs at the splice acceptor site leading to disrupt mRNA splicing [25].…”
Section: Discussionsupporting
confidence: 72%
“…In the present study, we found 17OHD patients carrying mutations previously described in Brazilian patients [6,25,33] suggesting possible founder effect. The intron 2 IVS2-2A > C mutation occurs at the splice acceptor site leading to disrupt mRNA splicing [25].…”
Section: Discussionsupporting
confidence: 72%
“…The patients were compound heterozygous carriers for p.Arg362Cys and p.Trp406Arg, previously described as prevalent in Brazil [Martin et al, 2003;Costa-Santos et al, 2004;Belgini et al, 2010]. Their parents were mutation carriers.…”
Section: © 2017 S Karger Ag Baselmentioning
confidence: 99%
“…DNA from 6 Brazilian patients in whom CYP17A1 mutations had previously been described [Martin et al, 2003;Costa-Santos et al, 2004;Belgini et al, 2010] were resequenced to further characterize 8 polymorphic CYP17A1 sequence variations in the 5 ′ UTR, exon 1, intron 2, intron 5, intron 6, and intron 7 regions, and resulting haplotypes were compared between the Brazilian and Spanish families.…”
Section: Cytogenetic and Molecular Studiesmentioning
confidence: 99%
“…The result is that progesterone and corticosterone are particularly increased in the circulation (Figures 3 and 4) 59 . Of note, in addition to both cortisol and C19 steroids in general being equally depressed in these individuals (see for instance 60; 61 ), 17-hydroxyprogesterone is diminished in contrast to clear elevation of progesterone in these subjects (Figures 3 and 4). …”
Section: ) the Search For A Selective 1720 Lyase Inhibitor – Is It mentioning
confidence: 82%